Analisis penilaian kinerja keuangan dengan pendekatan economic value added dan Market value added pada perusahaan telekomunikasi yang terdaftar di BEI tahun 2020-2022 - Lestari, Fitri Ayu; Musriati, Titik; Priantono, Seger (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Bima, 2024)
This study aims to determine the financial performance of telecommunications companies listed on the Indonesia stock exchange using EVA and MVA methods. This type of research is quantitative descriptive, with variables consisting of EVA and MVA. The population in this study is telecommunications companies listed on the IDX. Sample selection using purposive sampling and eleven companies were selected that met the criteria set by the researcher. Data is sourced from secondary data with a collection method using documentation. The results showed that there are ten companies whose Economic Value Added (EVA) value is positive or > 0, so it is said to be able to create economic added value for the company so that financial performance can be said to be good and there are seven companies that have a Market Value Added (MVA) value or > 0 indicating that the company is able to provide market added value for its shareholders so that financial performance can be said to be good. This study aims to determine the financial performance of telecommunications companies listed on the Indonesia stock exchange using EVA and MVA methods. This type of research is quantitative descriptive, with variables consisting of EVA and MVA. The population in this study is telecommunications companies listed on the IDX. Sample selection using purposive sampling and eleven companies were selected that met the criteria set by the researcher. Data is sourced from secondary data with a collection method using documentation. The results showed that there are ten companies whose Economic Value Added (EVA) value is positive or > 0, so it is said to be able to create economic added value for the company so that financial performance can be said to be good and there are seven companies that have a Market Value Added (MVA) value or > 0 indicating that the company is able to provide market added value for its shareholders so that financial performance can be said to be good.